The Role of the European Central Bank in a Sustainable Financial System - Nele Braun (Junior Management Science (JUMS), 2021)
The Paris Agreement acknowledged climate change as an urgent threat to the planet and human society. To fulfil the aim of limiting global warming, public and private investments and especially long-term investments are supposed to shift towards sustainable practices. Given the high investments required to pursue a sustainable financial system, it will be essential to involve the financial sector, as well as its participants and authorities. This thesis discussed the role the European Central Bank (ECB) could play in a transition towards a sustainable financial system. First, the framework conditions and the need for a sustainable financial system were explained, in particular the recent developments like for instance the introduction of the EU Taxonomy regulation, a classification system for sustainable activities which aims to provide clarity and limit the risk of green washing. After that, it was outlined how climate-related risks can spread to the financial system and why central banks are concerned of them. Three links for the relation between climate change and the financial system were identified – physical risks, transition risks and liability risks. In particular, the impact of climate change on price stability, financial stability and the portfolio management of central banks were examined. The objectives and the strategy of the ECB were described, to establish a base for the subsequent analysis of their instruments. Furthermore, the European Green Deal, an answer of the European Union to the challenges caused by climate change was presented.
Keywords: 650; Sustainable finance; green finance; central banking; sustainability